A perversão como sintoma social: leituras entre Freud e Melman - Barbosa, Juliana Falcão (2013)
This research aims to study perversion, approaching it as a social symptom. It integrates the line of research called Health, Clinic and Psychological Practices, understanding the clinic as a field of investigation through which it is possible to have access to the current social phenomena and discourse. This dissertation is composed by works with texts, in which we make explicit different forms of reading, and the texts are taken as objects of study. We carry a discussion about concepts related to the position of the author and the reader, reading, translation, interpretation and deconstruction. We work with research in psychoanalysis using a close and deconstructive reading strategy, based on the perspective that the meanings are built through the reading, in relation to, and dialoging with the text itself and with other readings. We discuss the social symptom concept, exposing how it is approached by different authors, aiming to connect it to perversion. We also register the associations made with texts by important authors in the field of psychoanalysis and in the approach of perversion. We opted to work, fundamentally, with two authors – Sigmund Freud and Charles Melman – who, coming from the psychoanalytical clinic, approach perversion in different ways. We did a deconstructive reading of the Three Essays on the Theory of Sexuality (1905) by Freud; and of the Man Without Gravity (2003), by Melman.